UTILIZATION OF WATER PLANTS AS MEDIA TO LOWER RAW WATER SALINITY CONSUMED BY PEOPLE IN SOUTH KALIMANTAN - Darmawan, Arief Rakhmad Budi (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Water is natural resource that is essential for life of all living things. Problems frequently encountered are the limited availability and difficulty to get clean water especially during dry season. One of the other problems is the high level of salt content (salinity) in most water consumed as a result of sea water intrusion. The objective of this research is to study the utilization of plants found on aquatic land or swamp land in the region of South Kalimantan as the media of reducing salt content in raw water sources for consumption water which is processed in installation of clean water. Plants used among others are water hyacinth (Eichhornia crassipes), giant salvinia (Salvinia molesta D. Mitch), water lettuce (Pistia stratiotes, Linn) and chinese water chestnut (Eleocharis dulcis). The research was conducted by using Completely Random Design (CRD) by putting the four plants each on a container filled first with salt solutions in concentration 1% (equivalent to 10,000 ppm). The time of observation was done on 7 days, 14 days and 21 days to identify the content of salt absorbed by and the effect on the plants. The data were analyzed using anova and were tested further using DMRT on 5% standard. The result showed that all water plants used were able to absorb salt in solution and reduce the salinity in different levels of the salt absorption. It was indicated that the content of salts had different between the top of the plants (the stalks and leaves) and the roots, the concentration of salt in the roots was larger. The test results indicated that up to 21 days observation, the absorption of salts upon chinese water chestnut, water hyacinth, water lettuce and giant salvinia, sequencially were : 5400 ppm (roots) and 2400 (stalks), 5216 ppm (roots) and 2700 (stalks), 3200 ppm (roots) and 1911 ppm (stalks) and also 4125 ppm (roots) and 1700 ppm (stalks).